Reflections on the accurate/inaccurate boundaries of museology (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
ln this article the concept of museology and its boundaries are analysed with the goal of starting a conceptual debate about this field of knowledge. Our premise is that the museum is not just a place to display old objects that are properly conserved and are exhibited to people at present, but a place for reflection and communication. Rather than finding the right statement, the aim is to contribute to the debate, identifying different perspectives to consider for its definition.This article ineludes the following themes: the museological object; a general perspective about the development of Chilean museology; reflections about the definition of museum and, finally, a seetion that eonsiders some general eonelusions.